Quality Evaluation of Marketed Formulation of Mouth Dissolving Ondansetron Tablets - Chinchore, Mayur V.; Surana, Santosh S.`; Maru, Avish D. (Asian Journal of Pharmaceutical Research and Development, 2014)
The main objective of this study was to compare the five brands of mouth dissolving tablets containing ondansetron, an antiemetic. Novel MDT technique provides the patient compliance and also meets the pharmaceutical needs such as improvement in the life cycle management over the convenient dosing especially for pediatrics, geriatrics and for psychiatric patients having difficulty in swallowing the conventional tablets and capsules dosage forms. For this study the mouth dissolving tablets were collected from market and were evaluated for hardness, friability, thickness, drug content, wetting time, weight variation test disintegration and in-vitro dissolution studies